Glucagon-like peptide-2 protects the gastric mucosa via regulating blood flow and metabolites - Zhang, Jing; Ning, Jing; Hao, Xinyu; Han, Xiurui; Fu, Wei; Gong, Yueqing; Meng, Qiao; Ding, Shigang; Zhang, Jing (Frontiers in Endocrinology, 2022)
Introduction Refractory peptic ulcers lead to perforation and hemorrhage, which are fatal. However, these remain a therapeutic challenge. Gastric mucosal blood flow is crucial in maintaining gastric mucosal health. It’s reported that Glucagon-like peptide-2 (GLP-2), a gastrointestinal hormone, stimulated intestinal blood flow. However, the direct role of GLP-2 in gastric mucosal blood flow and metabolites remain unclear. Here, we speculated that GLP-2 might protect the gastric mucosa by increasing gastric mucosal blood flow and regulating metabolites. This study was conducted to evaluate the role of GLP-2 in gastric mucosal lesions and its underlying mechanism. Methods We analyzed endogenous GLP-2 during gastric mucosal injury in the serum. Rats were randomly divided into two groups, with 36 rats in each group as follows: (1) normal control group (NC1); (2) ethanol model group (EC1); rats in EC1 and NC1 groups were intragastrically administered ethanol (1 ml/200 g body weight) and distilled water (1 ml/200 g body weight). The serum was collected 10 min before intragastric administration and 15, 30, 60, 90, and 120 min after intragastric administration. Furthermore, additional male Sprague–Dawley rats were randomly divided into three groups, with six rats in each group as follows: (1) normal control group (NC); (2) ethanol model group (EC); (3) 10 μg/200 g body weight GLP-2 group (GLP-2). Rats in the NC and EC groups were intraperitoneally injected with saline. Those in the GLP-2 group were intraperitoneally injected with GLP-2. Thirty minutes later, rats in the EC and GLP-2 groups were intragastrically administered ethanol (1 ml/200 g body weight), and rats in the NC group were intragastrically administered distilled water (1 ml/200 g body weight). After the intragastric administration of ethanol for 1 h, the animals were anesthetized and gastric mucosal blood flow was measured. Serum were collected for ultra performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) metabolomics. Results There were no significant change in endogenous GLP-2 during gastric mucosal injury (P<0.05). Pretreatment with GLP-2 significantly reduced ethanol-induced gastric mucosal lesions by improving the gastric mucosal blood flow, as examined using a laser Doppler flow meter, Guth Scale, hematoxylin-eosin staining, and two-photon microscopy. UPLC-MS/MS analyses showed that GLP-2 also maintained a steady state of linoleic acid metabolism. Conclusions Taken together, GLP-2 protects the gastric mucosa against ethanol-induced lesions by improving gastric mucosa blood flow and affecting linoleic acid metabolism.